Investigations on the Effects of a Passive Standing-from-Squatting and Gait Assistive Exoskeleton on Human Motion - Yu-Chih Lin; Sih-You Lin; Shih-Yu Kao (Bioengineering, 2025)
The aim of this study is to examine the biomechanical interaction between an assistive wearable exoskeleton and the human body. For this purpose, a passive exoskeleton is designed to provide support during the transition from a squatting position to standing, while also enabling the resilient components to become active during the initial and mid-swing phases of level walking. The active period can be adjusted by a slot, which triggers the activation of the resilient components when the exoskeleton’s flexion angle exceeds a critical value. This study also compares the effect of using different passive powered components in the exoskeleton. Electromyography (EMG) signals and angular velocity during human motion are collected and analyzed. Experimental results indicate that the designed assistive exoskeleton effectively reduces muscle effort during squatting/standing motion, as intended. The exoskeleton reduces the flexion/extension (x-axis) angular velocity during both squatting/standing and the swing phase of gait. The oscillation of the angular velocity curve about the y-axis during gait is larger without the exoskeleton, suggesting that the exoskeleton may introduce interference but also a stabilizing effect in certain dimensions during gait. This study provides a stronger foundation for advancing the design of both passive and active powered exoskeletons.